Scorecard - An innovative simplified tool to supplement the existing monitoring mechanism to assess and improve performance of antiretroviral treatment centers - Sudhir Chawla; Bhautik Modi; Bharat Bhusan Rewari; Pramod B Verma; Sonia Chetandas Chhabra (Wolters Kluwer Medknow Publications, 2017)
Introduction: All 26 antiretroviral treatment (ART) centers of Gujarat were monitored by Gujarat State AIDS Control Society under the National AIDS Control Program. A comprehensive tool is needed to identify gap in service delivery and to prioritize monitoring visits. Objectives: To supplement the existing monitoring system, identify strengths/weakness of ART centers, and give recommendations. Methodology: Scorecard was developed in spreadsheet format with 17 scoring indicators on monthly base from March 2014 onward. The centers were classified in three color zones: green (score ≥80%), yellow (score <80% and ≥50%), and red (score <50%). Visits were prioritized at centers with more indicators in yellow/red zone. The performance of centers was compared for March 2014 and March 2015. Results: The statistically significant improvement was observed in indicator "ART initiation within 2 months of eligibility," while after removing red zone from analysis, four more indicators named "eligible patients transferred out before ART initiation, general clients started on ART, antenatal women started on ART, and pre-ART follow-up CD4 done" reflect statistically significant improvement. Quadrant analysis was done for some indicators, which provide insight that less number of eligible patients may be a reason for low initiation of ART at one center, and at four other centers, the possible reasons for low retention are high death rate and high lost to follow-up rate. Based on these findings, the recommendations were made to regular mentoring centers, improve coordination between ART center and care and support centers (CSCs), and conduct verbal autopsy. Conclusion: Scorecard is a simple and cost-effective tool for monitoring, and by highlighting low-performing indicators, it helps in improving quality of services provided at ART centers.